RELATIONSHIP BETWEEN THE HABIT OF BRINGING LUNCH AND THE LEVEL OF MACRONUTRIENT ADEQUACY IN STUDENTS OF SMP N 2 EAST KARAWANG - Irdayanti, Haipa; Sefrina, Linda Riski; Elvandari, Millyantri (HEARTY, 2025)
The habit of bringing lunch is one effort to fulfill nutritional needs. Macronutrient intake is one of the main components that plays an important role in improving the nutritional status of students. This study aims to determine the relationship between the habit of bringing lunch and the level of energy and macronutrient adequacy in SMP N 2 East Karawang students. This research method is quantitative with a cross-sectional design. This study was conducted on 35 students of SMPN 2 East Karawang. The habit of bringing lunch was assessed with the Food Frequency Questionnaire (FFQ) form and intake was assessed using a 1x24-hour food recall interview then descriptive analysis was carried out using SPSS. Most students habitually bring lunch rarely (57.1%). The level of energy adequacy of students. The adequacy level of energy and macronutrients is mostly included in the deficient category, for energy (68.6%), protein (71.4%), fat (48.6%), and carbohydrates (68.6%). There was a significant relationship between the level of adequacy of energy (p=0.003 <0.05) and carbohydrates (p=0.037 <0.05). However, there was no significant relationship between the adequacy level of protein (p=0.707 < 0.05) and fat (p=0.603 < 0.05) in students of SMPN 2 East Karawang. This study concludes that there is a significant relationship between the habit of bringing lunch with the level of adequacy of energy and carbohydrates in students of SMPN 2 East Karawang.